Roofscapes: Narrative Geographies of Fugitive Praxis - Kelley, Elleza (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2023)
This article reads several works of African American literature that depict the urban roofscape as a site of contemporary fugitive praxis, made in and against the enclosures of 20th century urban space. The forms of freedom rehearsed on the roof are intersecting, overlapping and, at times, contradictory. Ultimately, I argue that the roofscape offers an analytic object through which to explore the thorny questions of property, gender, enclosure, and mobility—questions that enrich and complicate the study of fugitive geographies and their use as models for escaping and living outside of the violent enclosures of gendered racial capitalism. The multivalence of the rooftop provides an opportunity to dwell with the complex questions of fugitive method: What forms do geographies of fugitivity take? Who do they limit or enable? And under what conditions? How do fugitive geographies both sustain and break from the social, political, and economic relations from which their producers flee?